Integr. Business Fund. W/ Ethics and Law in Mngt. - AD2347 - 202101 - Mac Lean Martins, Ana Cecilia María (2021)
Course Overview ¿Life moves pretty fast. If you don't stop and look around once in a while, you could miss it.¿ -Ferris Bueller, Ferris Bueller¿s Day Off This class is about stopping to look around. We all believe we are ethical, law-abiding citizens, but research has shown that we are easily influenced into acting contrary to our professed values. As you will soon learn, none of us are immune to these tendencies. However, the good news is that by understanding how these subconscious vulnerabilities affect us, we can become aware of them and prevent them from leading us into poor decisions. As we open our eyes to the ethical and legal dimensions of seemingly mundane workplace activities, we gain the ability to make better decisions. Decisions that save money, avoid scandal, promote healthy cultures, and enhance our own reputations. These are good outcomes! In this class, we will explore a number of legal and ethical issues and try to bring them all together to help you become more aware and a more responsible business professional. Prerequisite Requirements BNAD 314R, MKTG 361, FIN 311, MIS 304 are prerequisite requirements for MGMT 402.